Cardiac adaptations in young triathletes: a 9-month longitudinal study during the peak height velocity period - Anthony Birat; Sébastien Ratel; Yoann M. Garnier; Alexis Dupuy; Alexandre Dodu; Claire Grossoeuvre; Anne-Charlotte Dupont; Mélanie Rance; Claire Morel; Stéphane Nottin (European Journal of Applied Physiology, 2025)

Inter-comparison and validation against in-situ measurements of satellite estimates of incoming solar radiation for Central Africa: From the annual means to the diurnal cycles - Amine Ouhechou; Nathalie Philippon; Béatrice Morel; Jörg Trentmann; Alexandre Graillet; Armand Mariscal; Yann Nouvellon (Atmospheric Research, 2023)

Evolution of the rice blast pathogen on spatially structured rice landraces maintains multiple generalist fungal lineages - Sajid Ali; Pierre Gladieux; Sebastien Ravel; Henri Adreit; Isabelle Meusnier; Joelle Milazzo; Sandrine Cros‐Arteil; François Bonnot; Baihui Jin; Thomas Dumartinet; Florian Charriat; Alexandre Lassagne; et al. (Molecular Ecology, 2023)
Traditional agrosystems, where humans, crops and microbes have coevolved over long periods, can serve as models to understand the ecoevolutionary determinants of disease dynamics and help the engineering of durably resistant agrosystems. Here, we investigated the genetic and phenotypic relationship between rice ( Oryza sativa ) landraces and their rice blast pathogen ( Pyricularia oryzae ) in the traditional Yuanyang terraces of flooded rice paddies in China, where rice landraces have been grown and bred over centuries without significant disease outbreaks. Analyses of genetic subdivision revealed that indica rice plants clustered according to landrace names. Three new diverse lineages of rice blast specific to the Yuanyang terraces coexisted with lineages previously detected at the worldwide scale. Population subdivision in the pathogen population did not mirror pattern of population subdivision in the host. Measuring the pathogenicity of rice blast isolates on landraces revealed generalist life history traits. Our results suggest that the implementation of disease control strategies based on the emergence or maintenance of a generalist lifestyle in pathogens may sustainably reduce the burden of disease in crops.

The ecologically relevant genetics of plant–plant interactions - Claude Becker; Richard Berthomé; Philippe Delavault; Timothée Flutre; Hélène Fréville; Stéphanie Gibot-Leclerc; Valérie Le Corre; Jean-Benoit Morel; Nathalie Moutier; Stéphane Muños; Céline Richard-Molard; James Westwood; et al. (Trends in Plant Science, 2023)

Quantifying the energetic cost of food quality constraints on resting metabolism to integrate nutritional and metabolic ecology - Thomas Ruiz; Apostolos‐Manuel Koussoroplis; Michael Danger; Jean‐Pierre Aguer; Nicole Morel‐Desrosiers; Alexandre Bec (Ecology Letters, 2021)
Consumer metabolism controls the energy uptake from the environment and its allocation to biomass production. In natural ecosystems, available energy in food often fails to predict biomass production which is also (co)limited by the relative availability of various dietary compounds. To date, the link between energy metabolism and the effects of food chemical composition on biomass production remains elusive. Here, we measured the resting metabolic rate (RMR) of Daphnia magna along ontogeny when undergoing various (non‐energetic) nutritional constraints. All types of dietary (co)limitations (Fatty acids, Sterols, Phosphorus) induced an increase in mass‐specific RMR up to 128% between highest and lowest quality diets. We highlight a strong negative correlation between RMR and growth rate indicating RMR as a promising predictor of consumer growth rate. We argue that quantifying the energetic cost imposed by food quality on individual RMR may constitute a common currency enabling the integration of nutritional and metabolic ecology.

U‐shaped response Unifies views on temperature dependency of stoichiometric requirements - Thomas Ruiz; Apostolos‐Manuel Koussoroplis; Michael Danger; Jean‐Pierre Aguer; Nicole Morel‐Desrosiers; Alexandre Bec (Ecology Letters, 2020)
Temperature and nutrient availability, which are major drivers of consumer performance, are dramatically affected by global change. To date, there is no consensus on whether warming increases or decreases consumer needs for dietary carbon (C) relatively to phosphorus (P), thus hindering predictions of secondary production responses to global change. Here, we investigate how the dietary C:P ratio optimising consumer growth ( TER C:P : Threshold Elemental Ratio) changes along temperature gradients by combining a temperature‐dependent TER C:P model with growth experiments on Daphnia magna . Both lines of evidence show that the TER C:P response to temperature is U‐shaped. This shape indicates that consumer nutrient requirements can both increase or decrease with increasing temperature, thus reconciling previous contradictive observations into a common framework. This unified framework improves our capacity to forecast the combined effects of nutrient cycle and climatic alterations on invertebrate production.

A microcalorimetric approach for investigating stoichiometric constraints on the standard metabolic rate of a small invertebrate - Thomas Ruiz; Alexandre Bec; Michael Danger; Apostolos‐Manuel Koussoroplis; Jean‐Pierre Aguer; Jean‐Pierre Morel; Nicole Morel‐Desrosiers (Ecology Letters, 2018)
Understanding the determinants of metabolism is a core ecological topic since it permits to link individual energetic requirements to the ecology of communities and ecosystems. Yet, besides temperature, metabolic responses to environmental factors remain poorly understood. For example, it is commonly assumed that dietary stoichiometric constraints increase metabolism of small invertebrates despite scarce experimental support. Here, we used microcalorimetric measurements to determine the standard metabolic rate ( SMR ) of Daphnia magna fed stoichiometrically balanced (C/P: 166) or imbalanced (C/P: 1439). Daphnids fed imbalanced maintained their stoichiometric homeostasis within narrow boundaries. However, they consistently increased their SMR while decreasing their growth rate. Our measurements demonstrate that homeostatic regulation implies higher metabolic costs, thereby reducing available energy for growth. We demonstrate that microcalorimetry is a powerful and precise tool for measuring small‐sized organisms’ metabolic rate, thus opening promising perspectives for understanding how environmental factors, such as nutritional constraints, affect organismal metabolism.

Is the meiofauna a good indicator for climate change and anthropogenic impacts? - Daniela Zeppilli; Jozée Sarrazin; Daniel Leduc; Pedro Martinez Arbizu; Diego Fontaneto; Christophe Fontanier; Andrew J. Gooday; Reinhardt Møbjerg Kristensen; Viatcheslav N. Ivanenko; Martin V. Sørensen; Ann Vanreusel; Julien Thébault; et al. (Marine Biodiversity, 2015)

Cotyledonary somatic embryos of Pinus pinaster Ait. most closely resemble fresh, maturing cotyledonary zygotic embryos: biological, carbohydrate and proteomic analyses - Alexandre Morel; Jean-François Trontin; Françoise Corbineau; Anne-Marie Lomenech; Martine Beaufour; Isabelle Reymond; Claire Le Metté; Kevin Ader; Luc Harvengt; Martine Cadene; Philippe Label; Caroline Teyssier; et al. (Planta, 2014)

Geological time formalization: an improved formal model for describing time successions and their correlation - Michel Perrin; Laura S. Mastella; Olivier Morel; Alexandre Lorenzatti (Earth Science Informatics, 2011)

Epac stimulation induces rapid increases in connexin43 phosphorylation and function without preconditioning effect - Nicolas Duquesnes; Mickael Derangeon; Mélanie Métrich; Alexandre Lucas; Philippe Mateo; Lin Li; Eric Morel; Frank Lezoualc’h; Bertrand Crozatier (Pflügers Archiv - European Journal of Physiology, 2010)